Fertilización con bayfolan suelo azul en el rebrote de Erythrina sp. “amasisa” y su efecto en el rendimiento del forraje en Zungarococha, Perú – 2022 - Lozano Flores, Ruben Francois (2023)
The production of vegetable protein with Fabaceae is one of the alternatives that farmers have been using in the humid tropics. The National University of the Peruvian Amazon in the Faculty of Agronomy is one of the concerns to carry out work in this line of research and is entitled FERTILIZATION WITH BAYFOLAN BLUE SOIL IN THE REGROUND OF Erythrina sp. "AMASISA" AND ITS EFFECT ON FORAGE YIELD IN ZUNGAROCOCHA, PERU - 2022. The evaluations were carried out 45 days after sowing with plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2 . With a Random Complete Block Design (D.B.C.A), with five treatments and four repetitions, the treatments under study were: T0 (0 kilos of Bayfolan/ha), T1 (50 kilos of Bayfolan/ha), T2 (100 kilos of Bayfolan nitrogen/ha) and T3 (150 kilos of Bayfolan/ha), obtaining the following results: that the T3 treatment (150 kilos of Bayfolan/ha) 45 days after the start of the research work gave in the yields of green matera (kg/m2) and dry matter (kg/m2), yields of 2752.75 g/m2 and 668.92 g/m2 respectively were achieved. In the yields of stems (g/m2) and leaves (g/m2), yields of 1086.75 g/m2 and 1666 g/m2 respectively were achieved. In the yields of green matter kg/ha, yields of 27527.5 kg/ha respectively were achieved.